Trends in growth and nutritional status of high school graduates in Hangzhou, China, 2011-2020 - Xu Duan; Yi-nan Zhou; Yun Chen (BMC, 2022)
Abstract Background During past decades, there was a positive trend in growth and nutrition status of adolescents in China, but there was significant regional disparity. The purpose of this study is to investigate the trends in growth and nutritional status of high school graduates in Hangzhou between 2011 and 2020. Methods High school graduates (Grade 12) who finished the physical examination of the national college entrance examination between 2011 and 2020 (n=481,353)were included in this study. Data were obtained from the database of physical examination of the national college entrance exam. Height and weight were measured; body mass index (BMI) was calculated from height and weight. Thinness, overweight and obesity were defined according to the International Obesity Task Force criteria. For the vast majority of the high school graduates were 18 years old or nearly 18 years old, the cutoffs of 18 years were adopted. Those are 18.5, 25 and 30 kg/m2, for thinness, overweight and obesity respectively. Results There was a significant growth trend in height, weight and BMI in both sexes (P < 0.001). Height increased by 1.80 cm in boys and 1.45 cm in girls. Weight increased by 4.62 kg in boys and 2.51 kg in girls. BMI increased by 1.09 kg/m2 in boys and 0.60 kg/m2 in girls. An increase trend was found in the prevalence of overweight and obesity in both sexes (P < 0.001). Overweight increased by 7.43% (from 9.05 to 16.48%) among boys and 4.05% (from 4.57 to 8.62%) among girls. Obesity increased by 3.85% (from 2.29 to 6.14%) among boys and 1.76% (from 0.64 to 2.40%) among girls. The prevalence of thinness fluctuated in both boys and girls, 12.42-15.59% among boys and 18.97-23.68% among girls. Boys had higher odds of overweight and obesity and lower odds of thinness than girls (P < 0.001). Conclusions There is a positive trend in growth and nutritional status of high school graduates in Hangzhou. However, there is still a considerable prevalence of thinness, it indicates a double burden of undernutrition and overnutrition.